Dryopteris juxtapostia Root and Shoot: Determination of Phytochemicals; Antioxidant, Anti-Inflammatory, and Hepatoprotective Effects; and Toxicity Assessment - Abida Rani; Muhammad Uzair; Shehbaz Ali; Muhammad Qamar; Naveed Ahmad; Malik Waseem Abbas; Tuba Esatbeyoglu (MDPI AG, 2022)
An estimated 450 species of Dryopteris in the Dryoperidaceae family grow in Japan, North and South Korea, China, Pakistan, and Kashmir. This genus has been reported to have biological capabilities; however, research has been conducted on Dryopteris juxtapostia. Therefore, with the present study, we aimed to exploring the biological potential of D. juxtapostia root and shoot extracts. We extracted dichloromethane and methanol separately from the roots and shoots of D. juxtapostia. Antioxidant activity was determined using DPPH, FRAP, and H2O2 assays, and anti-inflammatory activities were evaluated using both in vitro (antiurease activity) and in vivo (carrageenan- and formaldehyde-induced paw edema) studies. Toxicity was evaluated by adopting a brine shrimp lethality assay followed by determination of cytotoxic activity using an MTT assay. Hepatoprotective effects of active crude extracts were examined in rats. Activity-bearing compounds were tentatively identified using LC-ESI-MS/MS analysis. Results suggested that D. juxtapostia root dichloromethane extract exhibited better antioxidant (DPPH, IC50 of 42.0 µg/mL; FRAP, 46.2 mmol/g; H2O2, 71% inhibition), anti-inflammatory (urease inhibition, 56.7% at 50 µg/mL; carrageenan-induced edema inhibition, 61.7% at 200 µg/mL; formaldehyde-induced edema inhibition, 67.3% at 200 µg/mL), brine shrimp % mortality (100% at 1000 µg/mL), and cytotoxic (HeLa cancer, IC50 of 17.1 µg/mL; prostate cancer (PC3), IC50 of 45.2 µg/mL) effects than D. juxtapostia root methanol extract. D. juxtapostia shoot dichloromethane and methanol extracts exhibited non-influential activity in all biological assays and were not selected for hepatoprotective study. D. juxtapostia root methanol extract showed improvement in hepatic cell structure and low cellular infiltration but, in contrast the dichloromethane extract, did not show any significant improvement in hepatocyte morphology, cellular infiltration, or necrosis of hepatocytes in comparison to the positive control, i.e., paracetamol. LC-ESI-MS/MS analysis showed the presence of albaspidin PP, 3-methylbutyryl-phloroglucinol, flavaspidic acid AB and BB, filixic acid ABA and ABB, tris-desaspidin BBB, tris-paraaspidin BBB, tetra-flavaspidic BBBB, tetra-albaspidin BBBB, and kaempferol-3-O-glucoside in the dichloromethane extract, whereas kaempferol, catechin, epicatechin, quinic acid, liquitrigenin, and quercetin 7-O-galactoside in were detected in the methanol extract, along with all the compounds detected in the dichloromethane extract. Hence, D. juxtapostia is safe, alongside other species of this genus, although detailed safety assessment of each isolated compound is obligatory during drug discovery.